Midijob reform: Increased redistribution in pension insurance - noticeable costs, relief not well targeted - Hermann Buslei; Johannes Geyer; Peter Haan (DIW Weekly Report, 2023)
The German Federal Government has expanded subsidies for employees with low gross wages (midijob employees) as of January 1, 2023, and raised the upper earnings limit to 2,000 euros. As a result, around 6.2 million midijob employees will benefit from paying reduced social security contributions while still receiving their full pension entitlements, made possible by a redistribution within the social insurance funds. Such redistribution, however, contradicts the equivalence principle on which the pension insurance system is based. This Weekly Report investigates the financial scope of the additional pension entitlements and how targeted this subsidy is. The statutory pension insurance (Gesetzliche Rentenversicherung, GRV) will lose revenue of around one billion euros per year as a result of the reduced contributions. Due to the midijob regulation, pension contributions are on average twelve euros a month lower per person benefiting from the subsidy. However, when viewing the subsidy by net income or individual gross hourly wages, it can be seen that this policy is poorly targeted: Individuals with high net incomes or high hourly wages but low employment levels also benefit from the subsidy. If policymakers want to redistribute funds in the statutory pension insurance system, they should readjust the redistribution to make it more targeted. To combat old-age poverty more effectively, the pension entitlements of those at risk should be targeted directly or the basic pension supplement should be expanded.
Keywords: H24; H55; D31; 330; income distribution; social security contributions; low income